Improcedência liminar do pedido e sua importância no Novo Processo Civil - Kusumoto, Bruna (2019)
The present dissertation aims to study the changes brought to the institute of preliminary dismissal of the request by the New CPC / 2015, the expansion of the hypotheses of fit linked to the greater legal certainty, since the paradigm decisions for its application take place before formally binding precedents, as well as how to demonstrate its application within the legal system. In this regard, we will address the merits of the institute of the dismissal of the claim in actions originating in the courts. Still, it will seek to demonstrate the situations of the applicability of said institute in which the damage to the defendant is verified. To carry out the study and achieve the outlined objective, the methodology of bibliographic, doctrinal and jurisprudential research will be used, with qualitative approach